Artificial Manduca sexta forewings for flapping-wing micro aerial vehicles: how wing structure affects performance. (22nd September 2017) - Moses, K C; Michaels, S C; Willis, M; Quinn, R D
Abstract: A novel approach to fabricating and testing artificial insect wings has been developed. Utilizing these new techniques, locally harvested hawk moth ( Manduca sexta ) forewings are compared to engineered forewings with varying wing structures. A number of small, flexible engineered forewings were fabricated with identical planform size and shape but with variations in camber, ribbing, thickness and composition. A series of static and dynamic assessments compares the forewings in terms of structure and performance. Data from these experiments show that the fabrication method can produce artificial forewings with similar properties to that of M. sexta . Flexural stiffness (EI) data shows a maximum percent difference of 41% between the left and right natural M. sexta forewings, whereas engineered forewings have a maximum percent difference of 18%. When deflection is induced from the ventral side of the forewing, EI values are at least 9.1% higher than when it is induced from the dorsal side. According to simulations, approximately 57% of this difference can be attributed to the camber of the forewings. Fabricated forewings produced comparable amounts of lift to natural M. sexta forewings (1.00 gF and 0.96 gF at 25 Hz flapping frequency respectively).